PENENTUAN FENOLIK TOTAL, FLAVONOID TOTAL, DAN AKTIVITAS ANTIOKSIDAN EKSTRAK BAWANG LANANG (Allium sativum L.) - Dhini Tri Wilujeng; Mirwa Adiprahara Anggarani (Unesa Journal of Chemistry, 2021)
Free radicals are unstable molecules that can cause oxidative stress. Oxidative stress can lead to damage to cells, tissues, and organs, which can lead to degenerative diseases. Oxidative stress can be reduced by increasing the body's immunity through antioxidants, where these antioxidants can be found in one of the natural ingredients, namely single bulb garlic. The purpose of this study was to determine the potential of imported single bulb garlic with various solvents as a source of natural antioxidants based on total phenolic levels, flavonoids, and antioxidant activity. The Follin-ciocalteu method was used to determine total phenol, total flavonoids were determined colorimetrically with AlCl3, and antioxidant activity was determined by the DPPH (2,2-diphenyl-1-picryhydrazyl) method. The results showed that the total phenolic extract of ethanol 96%, ethyl acetate, and dichloromethane were 13.77 (medium); 26.60 (medium); and 6.36 (low) mg GAE/gr extract. The total flavonoids of ethanol 96% extract, ethyl acetate, and dichloromethane were 0.97; 2.88; and 0.47 mgQE / gr extract. Meanwhile, the antioxidant activity (IC50 value) for 96% ethanol extract was 339.69 ppm (weak), 174.03 ppm for ethyl acetate extract (medium), and 430.48 ppm for dichloromethane extract (weak). Based on the research results, it can be concluded that imported single bulb garlic with the three solvents have potential as a source of natural antioxidants, but the test results are no better than total phenolic, total flavonoids, and antioxidant activity of local single bulb garlic. Key words: Total Phenolic, flavonoid, antioxidant, single bulb garlic